Integrative diagnosis of the needle nematode Longidorus jonesi affecting forest in southern Japan. Issue 3 (28th March 2014) - Palomares‐Rius, J. E.; Kikuchi, T.; Cantalapiedra‐Navarrete, C.; Castillo, P.; Woodward, S.
Summary The occurrence of a parthenogenetic population of Longidorus jonesi in the rhizosphere of a Prunus sp. tree in a mixed evergreen forest is reported for the first time in Miyazaki (Miyazaki prefecture), southern Japan, and constitutes the first report of this species in Japan. Nematode diagnosis matched well with the original description in India and a subsequent report in China. Morphometric traits of the Japanese population were characterized by a longer odontostyle length (123–142.5 vs. 107–120 μm) and some differences in c ratio (95.9–131.5 vs. 140–185) with respect to the original description, but closer to the Chinese population. This difference could be considered as geographical intraspecific variability. Molecular characterization from nuclear ribosomal RNA genes [D2‐D3 expansion segments of large ribosomal subunit (28S) and internal transcribed spacer 1 (ITS1)] was provided for the first time. Molecular analysis of D2‐D3 and ITS1 showed a close relationship with L. diadecturus, a virus‐vector nematode, by 94 and 79% similarity, respectively. The similarities in morphology, molecular and ecology (L. jonesi and L. diadecturus are feeding mainly on Prunus species) suggest that this species could be a potential virus vector, as it is the case with L. diadecturus and peach rosette mosaic virus.